Teachers’ Perceptions of School Behavior Support Systems: A Case Study - Sarchet, Laura N. (Journal of the American Academy of Special Education Professionals, 2023)
Teachers at a public middle school were given a questionnaire assessing the supports for student behavior and emotional needs in their school and district. Results show that teachers at this middle school perceive themselves as highly effective in forming individual relationships with students. Areas of growth include more clearly communicating and consistently implementing a Response to Intervention (RtI) process for behaviors, clarifying expectations of student behavior for both staff and students, and providing staff with more proactive professional development related to working with students with Emotional and Behavior Disorders (EBD). Relationship- and community-building RtI supports (Jones et al., 2004; Morrissey et al., 2010) fit well into a schoolwide Positive Behavior Interventions and Supports (PBIS) program (Fairbanks et al., 2008). One teacher is a single entity within the context of an entire system, they can be an advocate for change within the building and continue to support students’ social, emotional, and behavioral learning.